Fast and robust adaptive beamforming algorithms for large-scale arrays with small samples - Zhang, Xue-Jun; Xie, Hu; Feng, Da-Zheng; Zheng, Wei Xing; Hu, Hao Shuang (Signal processing, 2021)
•A fast and robust beamforming algorithm for the large scale sensor array under small sample case.•Low computational complexity and easily implemented.•An efficiently and free parameter loading factor calculation method.•The performance of the proposed algorithm is superior to that of many other robust adaptive beamforming algorithms. The adaptive beamformer of large-scale sensor array mainly suffers from two limits. One limit is an insufficient number of training snapshots, which usually results in an ill-posed sample covariance matrix in many real applications. The other limit is the high computation complexity of the beamformer that severely restricts its online processing. To overcome these two limits, two fast and robust adaptive beamforming algorithms are proposed in this paper, which refers to the linear kernel approaches and formulates the weight vector as a linear combination of the training samples and the signal steering vector. The proposed algorithms only need to calculate a low-dimensional combination vector instead of the high-dimensional adaptive weight vector, which remarkably reduces the computation complexity. Moreover, regularization techniques are utilized to suppress the excessive variation of the combination vector caused by an underdetermined estimation of the Gram matrix. Experimental results show that the proposed algorithms achieve better performance and lower computation complexity than algorithms in the literature. Especially, like the kernel approaches, the proposed algorithms achieve good performance under the small sample case.